Pollen morphology of section Cheirolepis Boiss. of the genus Centaurea L. (Asteraceae) in Turkey - Çitak, Burcu Yilmaz; Dural, Hüseyin; Uysal, Tuna; Pinar, Nur Münevver (Bangladesh Journal of Plant Taxonomy, 2019)
In this paper, the palynomorphology of 17 taxa of section Cheirolepis in Turkey, were investigated by light (LM) and scanning electron microscope (SEM). Detailed descriptions of the pollen grains were given for each taxon and a well-resolved dendrogram was generated through numerical analysis of palynological diagnostic features. The pollen grains were found to be radially symmetric, isopolar, and generally 3-zonocolporate, with the exception of C. derderiifolia, C. kotschyi var. floccosa, and C. saligna, which were also 4-zonocolporate. The shape of the pollen grains were prolatespheroidal, with the polar axes of 32.76–46.26 μm and equatorial axes of 31.86–45.82 μm. The sculpturing of the pollen grains was generally scabrate-perforate or rarely microechinate-perforate. The spines were conical with a changing base length. The length and the width of the spines varied between 0.48 and 2.28 μm and 0.4 and 3.39 μm, respectively. The number of perforations at the base of the spines ranged in two or more rows and they varied between 5 and 30. The number of spines was 16–70 in 10 μm2. The results of this study showed that the polar axes, equatorial axes, aperture type, pollen shape, spine length, perforation number, and number of spines in 10 μm2 are essential for distinguishing the studied taxa. The taxa were grouped by clustering analysis of selected pollen characters using the UPGMA method.